Low-dose aspirin and the severity of ıschemic colitis: A single-center retrospective study - Xiao, Weiming; Zhou, Shuai yang; Wu, Keyan; Deng, Bin; Wu, Dacheng; Wang, Yuanzhi; Gong, Weijuan; Ding, Yanbing; Lu, Guotao (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To evaluate the effect of low-dose aspirin (50-150 mg/d) on the severity of ischaemic colitis. Materials and Methods: A total of 244 patients admitted to our hospital for ischaemic colitis were included in the study between 2013 and 2018. Patients were divided into an aspirin group and a non-aspirin group based on recent aspirin use history before ischaemic colitis onset. Clinical performance, biochemical indices, and endoscopic findings were compared. Results: The average age and the proportion of underlying disease including hypertension, cerebral infarction, and coronary heart disease in the aspirin group was significantly higher than those in non-aspirin group were (p<0.05). In terms of clinical symptoms, the proportion of diarrhea in aspirin group was significantly higher than that in non-aspirin group, but the proportion of abdominal pain was significantly reduced. Colonoscopy results showed that the incidence of ulceration was significantly higher in the aspirin group than in the non-aspirin group (p<0.05). Conclusion: The use of low-dose aspirin may aggravate the severity and mask the symptoms of abdominal pain in ischaemic colitis.